Restricted Omniscience and Ways of Knowing - Byerly, T. Ryan (Sophia, 2014)
Recently, several philosophers have moved from a classical account of divine omniscience according to which God knows all truths to a restricted account of divine omniscience according to which God knows all knowable truths. But an important objection offered by Alexander Pruss threatens to show that if God knows all knowable truths, God must also know all truths. In this paper, I show that there is a way out of Pruss’s objection for the advocate of restricted omniscience if she will define her view in terms of ways of knowing rather than in terms of logical possibilities.